Sharing resources within the household: A multi-country microsimulation analysis of the determinants of intrahousehold strategic weight differentials and their distributional outcomes - Kristian Orsini; Amedeo Spadaro (University of Essex, Institute for Social and Economic Research (ISER), 2005)
Equal intra-household sharing is still assumed by the vaste majority of applied analyses in welfare economics. Few pieces of work have tried to depart from the equal sharing hypothesis, but their impact has been limited by lack of data or restricted application to special cases. This paper proposes a new framework to derive sharing rules based on individual bargaining power. The latter is deÖned for each household member as the share of resources gained by the household due to his/her presence. The causes of power dierentials and their impact on income distribution are analysed in four EU countries presenting signiÖcantly dierent tax-beneÖt systems: Finland, Italy, Germany and the United Kingdom.
Keywords: C70; D1; J16; H31; 330; intra-household sharing; tax-benefit systems; microsimulation